EVALUASI TATA KELOLA INFRASTRUKTUR TEKNOLOGI INFORMASI PADA UMKM KULINER RYUDON CAFE & RESTO MENGGUNAKAN FRAMEWORK COBIT 2019 - Vionetha Lavega; Vivian Vivian; Agnes Monica; Michella Valery; Calista Silvia Jaya; Dicky Pratama (CV. Denasya Smart Publisher, 2026)
The use of information technology (IT) in the culinary business sector has become increasingly essential to support service efficiency, transaction accuracy, and operational data security. Nevertheless, many micro, small, and medium enterprises (MSMEs) still experience limitations in implementing structured and well-documented IT governance. This study aims to evaluate the governance of IT infrastructure at Ryudon Cafe & Resto, an MSME in the culinary sector, using the COBIT 2019 framework. The evaluation focuses on four selected domains: DSS01 (Manage Operations), DSS02 (Manage Service Requests and Incidents), DSS05 (Manage Security), and BAI09 (Manage Assets). This research adopts a qualitative case study approach, with data collected through observations and interviews. The results indicate that IT operational activities have not been formally documented, service incidents are not systematically recorded, security controls are implemented informally, and IT asset management lacks an official inventory. These conditions suggest potential risks to operational continuity and information security. Based on the findings, several recommendations are proposed, including the development of standard operating procedures (SOPs), incident logging mechanisms, formal security policies, and structured IT asset inventories. The study demonstrates that COBIT 2019 can be effectively applied within MSME environments as a practical framework to strengthen IT governance and support sustainable organizational development.